2002
DOI: 10.1046/j.1440-6047.2002.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐dosage vitamin A and riboflavin on iron‐folate supplementation in anaemic pregnant women

Abstract: A double-blind, placebo, controlled trial was conducted in Banyudono subdistrict, Boyolali regency, Central Java province, Indonesia. The aim of the study was to determine whether adding low-dosage vitamin A and riboflavin can enhance the effect of iron-folate supplementation in anaemic pregnant women. From July to November 2000, 202 pregnant women were screened for anaemia (haemoglobin < 11.0 g/dL). One hundred and three pregnant women (51%) were found to be anaemic and were then allocated alternately into fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 7 publications
1
21
0
1
Order By: Relevance
“…Pregnant women in rural China with low hemoglobin status (80-105 g/L) showed an enhanced hematologic response to a combined supplement of iron, folic acid, retinol, and riboflavin for 2 mo than to a supplement of iron and folic acid alone (33). Studies in mildly anemic populations in Indonesia showed that a supplement of riboflavin enhanced the increase in hemoglobin seen in response to conventional hematinics alone (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women in rural China with low hemoglobin status (80-105 g/L) showed an enhanced hematologic response to a combined supplement of iron, folic acid, retinol, and riboflavin for 2 mo than to a supplement of iron and folic acid alone (33). Studies in mildly anemic populations in Indonesia showed that a supplement of riboflavin enhanced the increase in hemoglobin seen in response to conventional hematinics alone (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…After supplementation, the proportion of women who became non-anaemic was 35% in the vitamin A-supplemented group, 68% in the iron-supplemented group, 97% in the group supplemented with both, and 16% in the placebo group. Therefore this study concluded that improvement in vitamin A status may contribute to the control of anemia in pregnant women (Suprapto et al, 2002).…”
Section: Vitamin a Supplementationmentioning
confidence: 72%
“…251 women aged 17-35 years, parity 0-4, gestation 16-24 weeks and hemoglobin between 80 and 109 g/L were randomly allocated to four groups: vitamin A (2.4 mg retinol) and placebo iron tablets; iron (60 mg elemental iron) and placebo vitamin A ; vitamin A and iron; or both placebos, all daily for 8 weeks (Suprapto et al, 2002). Maximum hemoglobin was achieved with both vitamin A and iron supplementation (12.78 g/L, 95% , with one third of the response attributable to vitamin A (3.68 g/L, 95% CI 2.03-5.33) and two thirds to iron (7.71 g/L,.…”
Section: Vitamin a Supplementationmentioning
confidence: 99%
“…Clinical trials involving children, adolescents, pregnant and lactating women were developed in different regions of the world and most of them reported a significant impact of VA supplementation/fortification on Hb and other iron parameters [3,6,10,11,12,13,14,15,16,17,18]. However, the effect of VA supplementation/fortification on iron status should be taken with caution due to differences between populations in terms of VA and Fe status, age of the individuals, type of supplementation or fortification, and duration of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Suprapto et al [17] evaluated the impact of adding low dose of VA (5000 IU) together with other micronutrients as a routine supplementation for 84 anemic Indonesian pregnant women (Hb < 110 g/L) in a placebo-controlled clinical trial. The women were allocated into the following groups: VA (5000 IU) + Fe (60 mg) + folic acid (250 μg) + riboflavin (5 mg); VA (5000 IU) + Fe (60 mg) + folic acid (250 μg); Fe (60 mg) + folic acid (250 μg) + riboflavin (5 mg); Fe (60 mg) + folic acid (250 μg) + placebo.…”
Section: Methodsmentioning
confidence: 99%